Descriptive Analysis and ANOVA Test with File Sending on Computer Networks Attacked with Rogue's Dynamic Host Configuration Protocol (DHCP) - Hero Wintolo; Yuliani Indrianingsih; Wahyu Hamdani; Syafrudin Abdie (Universitas Ahmad Dahlan, 2023)
The requirement for a computer that is physically connected to a computer network to be able to access existing resources on a computer network in the form of an IP address obtained statically or dynamically. On a static IP address, there are not many problems that arise because it is loaded directly into the computer, while for a dynamic IP address, security problems arise in the form of a dynamic IP address sharing server in the form of DHCP Rogue. The configuration that is added to the first router when the network is hit by a DHCP rogue attack is to configure the main router, in this case, the first router, and the switch used as a connecting device between computers. configuration on both switches is done by snooping trust which is useful for securing IP addresses to avoid IP attackers. This research was conducted to find out if a computer network with a dynamic IP address was attacked by sending files between computers. Files with the longest sending time indicate an attack on the computer network. The method used in this study is the ANOVA test with descriptive-based analysis. Based on the results of the analysis, it is known that the average file transfer time on networks affected by DHCP Rogue is higher than the average file transfer time on normal and mitigated networks, and the significant value of the ANOVA test results has a value of 0.004. In general, it can be concluded that there are differences in data transfer when the network is normal, the network is subject to DHCP Rogue, and the network has been mitigated with DHCP Rogue.